Purification and electrical characterisation of nanotube and nanowire - polymer composites - Murphy, Robert (Trinity College (Dublin, Ireland). School of Physics, 2006)
The yield and purity of multiwalled carbon nanotube (MWNT) soot was maximised by control of production parameters. The optimal production parameters were found to be J = 190 A/cm2 and P = 500 Torr achieving a yield of up to 24mg/min with an approximate MWNT purity of 55% as measured by electron spin resonance (ESR).
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin